To find the total cost of renting the bike, we need to combine the fixed charge of $13 with the hourly cost of $4 per hour for h hours.
The total cost can be expressed as:
\[ \text{Total Cost} = \text{Fixed Charge} + (\text{Hourly Rate} \times \text{Hours}) \] \[ \text{Total Cost} = 13 + 4h \]
According to the problem, Mateo rented the bike for a total of $37. Therefore, we can set up the equation:
\[ 13 + 4h = 37 \]
Now, if we rearrange this equation to isolate \(4h\), we subtract 13 from both sides:
\[ 4h = 37 - 13 \] \[ 4h = 24 \]
The equation that represents this situation is:
\[ 4h + 13 = 37 \]
So the correct response is:
4h + 13 = 37
(4 h plus 13 is equal to 37)